Factors Affecting Employees’ Commitment In Manufacturing Company - Senin, Nurul Syahirah; Rashid, Umi Kartini; Nasuredin, Juzaimi (Research in Management of Technology and Business, 2021)
Employee commitment is vital to an organization and has an impact on employee's performance. The purpose of this study was to investigate the factors that impacted the employee’s commitment. Employees in the private sector made up the majority of those who took part in this survey. This study was conducted quantitatively and questionnaires were sent to 204 employees. The obtained data were analysed, and descriptive and correlation scores were gained. The results discovered that employee’s commitment level was high. Knowledge sharing was the dominating element that influenced the employee’s commitment and showed the highest mean value based on the mean value. This result also revealed that compensation and incentives, training and development, and knowledge sharing affected employee’s commitment in the manufacturing company.